Transfer of Staurosira grunowii to Staurosirella - MORALES, EDUARDO A.; BUCZKÓ, KRISZTINA; WETZEL, CARLOS E.; NOVAIS, MARIA HELENA; OGNJANOVA-RUMENOVA, NADJA; HOFFMANN, LUCIEN; ECTOR, LUC (Taylor & Francis Group, 2014)
The new combination Staurosirella grunowii (Pantocsek) E. Morales, Buczkó & Ector comb. nov. is presented based on a detailed analysisof fossil material from Lutila, Slovakia using light and scanning electron microscopy. The species is widely known as Staurosira harrisoniivar. amphitetras Grunow. Striae bearing well-developed vimines delimiting typically long areolae, thick virgae-bearing spines, developedapical pore ﬁelds composed of simple round poroids and open girdle bands with valvocopula-bearing ﬁmbriae are some of the features thatlink this taxon to species currently ascribed to Staurosirella D.M. Williams & Round. The taxon is readily distinguished by its tetra-angularshape, which is not seen in any other species within this genus. An analysis of the morphology of this taxon together with its nomenclaturalhistory is presented herein
Keywords: araphid diatoms; Bacillariophyta; fossil; Pantocsek collection; Slovakia; Staurosirella grunowii; ype material